Disruption of HLA class II antigen presentation in Burkitt lymphoma: implication of a 47 000 MW acid labile protein in CD4+ T‐cell recognition. Issue 3 (July 2014) - God, Jason M.; Zhao, Dan; Cameron, Christine A.; Amria, Shereen; Bethard, Jennifer R.; Haque, Azizul
Summary While Burkitt lymphoma (BL) has a well‐known defect in HLA class I‐mediated antigen presentation, the exact role of BL‐associated HLA class II in generating a poor CD4+ T‐cell response remains unresolved. Here, we found that BL cells are deficient in their ability to optimally stimulate CD4+ T cells via the HLA class II pathway. This defect in CD4+ T‐cell recognition was not associated with low levels of co‐stimulatory molecules on BL cells, as addition of external co‐stimulation failed to elicit CD4+ T‐cell activation by BL. Further, the defect was not caused by faulty antigen/class II interaction, because antigenic peptides bound with measurable affinity to BL‐associated class II molecules. Interestingly, functional class II–peptide complexes were formed at acidic pH 5·5, which restored immune recognition. Acidic buffer (pH 5·5) eluate from BL cells contained molecules that impaired class II‐mediated antigen presentation and CD4+ T‐cell recognition. Biochemical analysis showed that these molecules were greater than 30 000 molecular weight in size, and proteinaceous in nature. In addition, BL was found to have decreased expression of a 47 000 molecular weight enolase‐like molecule that enhances class II‐mediated antigen presentation in B cells, macrophages and dendritic cells, but not in BL cells. These findings demonstrate that BL likely has multiple defects in HLA class II‐mediated antigen presentation and immune recognition, which may be exploited for future immunotherapies.